Dysbiosis of Gut Microbiota and Lipidomics of Content Induced by Dietary Methionine Restriction in Rice Field Eel (Monopterus albus) - Hu, Yajun; Cai, Minglang; Chu, Wuying; Hu, Yi (Frontiers in Microbiology, 2022)
An 8-week feeding trial was conducted using the rice field eel (Monopterus albus) with six isonitrogenous and isoenergetic experimental diets of basic feed supplemented with different levels of methionine (0, 2, 4, 6, 8, or 10 g/kg). This study built upon previous research findings that showed dietary methionine restriction (M0, 0 g/kg) inhibited hepatic fatty acid metabolism and intestinal fatty acid transportation, but both are improved by dietary supplementation with a suitable level of methionine (M8, 8 g/kg). Hence, M0 and M8 were selected to investigate how methionine regulates the gut microbiota and lipidomics of M. albus. Compared with M0, values for gut bacterial Sobs, Shannon, ACE, and Chao1 indices of M8 were remarkably increased (p < 0.05), with Fusobacteria, Firmicutes, and Proteobacteria the dominant phyla and Cetobacterium, Plesiomonas, and Bacillus the main genera in the community under the M0 vs. M8 treatments. However, compared with M0, the proportion of phyla consisting of Fusobacteria decreased in M8, as did the Cetobacterium and Lactococcus at the genus level; conversely, the proportions corresponding to Firmicutes, Proteobacteria, and Chioroflexi phyla increased in M8, as did the Clostridium and Streptococcus genera. Many edges appeared in the circus and networks, demonstrating the interspecies interactions among different operational taxonomic units (OTUs). In addition, various OTUs within the same phylum were clustered within one module. Cooperative interactions were predominant in the two networks, while competitive interactions were prevalent in their submodules. Gut microbiota mainly played roles in nutrition (lipid, amino acid, and carbohydrate) transport and metabolism under the M0 vs. M8 treatments. The PLS-DA scores indicated a significant difference in the main lipidomic components between the M0 and M8 treatment groups. Namely, the TG(26:0/16:0/17:0), TG(28:0/16:0/16:0), TG(26:0/16:0/16:0), and TG(30:0/16:0/16:0)—among others—comprising the gut content were reduced under the M8 treatment (p < 0.001). The genus Clostridium was positively correlated with TG(18:1/18:1/22:5), TG(16:0/17:0/18:1), TG(18:0/18:1/20:3), and other compounds, yet negatively correlated with TG(18:0/17:0/20:0), TG(16:0/17:0/24:0), and TG(16:0/16:0/24:0), among others as well. According to the lipidomics analysis, the predicted KEGG pathways mainly included lipid and glycan biosynthesis and metabolism, and digestive, sensory, and immune systems. In conclusion, methionine restriction disturbed the microbial community balance and induced microbial dysfunctions, whereas methionine supplementation improved the homeostasis of gut microbiota and lipid metabolism of the rice eel.